Ethyl cellulose particles loaded with α-tocopherol for inhibiting thermal oxidation of soybean oil. (15th January 2021) - Ma, Xin; Liu, Ying; Fan, Liuping; Yan, Weiqiang
Graphical abstract: Highlights: Ethyl cellulose particles loaded with α-tocopherol were successfully fabricated. Particle size decreased with increased viscosity of ethyl cellulose. Ethyl cellulose significantly improved thermal stability of α-tocopherol. The obtained particles had good dispersibility in soybean oil. Loaded particles effectively inhibited thermal oxidation of soybean oil. Abstract: Most endogenous antioxidants degrade and lose efficiency during frying. The study aimed to inhibit thermal oxidation of soybean oil by fabricating α-tocopherol loaded particles with ethyl cellulose (EC) of different viscosity grades (M9, M70 and M200) via anti-solvent method. As the viscosity of ethyl cellulose increased, particle size decreased from micrometer to nanometer. Confocal laser scanning microscope confirmed successful encapsulation and uniform distribution of α-tocopherol in the loaded particles. Differential scanning calorimetry and thermogravimetric analysis demonstrated that loaded particles protected α-tocopherol from oxidation and degradation. Meanwhile, Fourier transformed infrared demonstrated that α-tocopherol interacted with EC through hydrogen bond and hydrophobic effects. With excellent dispersibility in soybean oil, loaded particles effectively inhibited thermal oxidation of soybean oil and loaded M200 nanoparticles was the most effective, which performed far better than tert-butylhydroquinone (TBHQ). Therefore, the nanoparticles offered a promising way to enhance oxidative stability of oils during thermal processing.